(untitled) (REMUNOM, 2024)
Abstract Pressure injuries are still considered a serious problem, especially in the elderly and in the setting of chronic degenerative diseases. This study was based on a search for bibliographical works and articles on preventive and therapeutic actions by nurses published between 2013 and 2023, describing knowledge on the topic. Regarding the methodology, it was a literature review carried out through a descriptive bibliographic survey of nursing journals indexed in LILACS, MEDLINE, SCIELO AND GOOGLE ACADÊMICO. The material includes detailed readings that identify three areas of research: pressure injury prevention, pressure injury treatment, and pressure injury care. Finally, it is concluded that the prevention of pressure injuries is extremely important for the health and well-being of outpatients. In addition to investing in the training and continuing education of health professionals, standardization and compliance with prevention guidelines must be promoted. Implementing effective preventive measures can significantly reduce the incidence of pressure injuries and improve the quality of life of those affected.